Implementasi Pembelajaran Pendidikan Agama Hindu Dalam Pembentukan Karakter Anak Hindu Di Sekolah Dasar Negeri Surakarta - Setyaningsih Setyaningsih (Jayapangus Press, 2019)
This research is motivated by the reality of education in the present. The decline in the quality of education in Indonesia, which is less concerned with learners' affective education, has resulted in a decline in the morale of the younger generation, some actions that are not in accordance with values ​​and norms have become commonplace, such as corruption, juvenile delinquency, cheating, absent during school hours for students and so on. Some parties indicated that the decline in morality that occurred in Indonesia was one of them due to the low quality of education which lacked attention to character education for their students. This study aims to answer the problem: how the concept of learning Hinduism education in the formation of Hindu children's character, how the application of Hinduism education learning in the formation of Hindu children's character and how the implications of learning Hinduism education in forming the character of Hindu children in Surakarta City Elementary School. These problems are discussed with a qualitative approach, data collection techniques using participant observation, interviews and documentation. After the data is obtained through data collection techniques then the data is analyzed through the process of data management in the form of data reduction. The results of this study indicate that the implementation of learning Hinduism education in the formation of the character of Hindu children in Surakarta City Primary School is carried out with the planning and implementation stages. For the success of learning Hinduism education, Hindu teachers must also master good and comprehensive learning methodologies supported by adequate learning facilities and infrastructure. The success of learning programs in schools, especially in building the character of students, must be borne jointly by all school people starting from school leaders, teachers, employees, and active student involvement. In addition, schools must also involve parents of students and the entire community around the school to participate in supporting the success of the school in building the character of its students.